Delicta graviora contra mores in De delictis reservatis Norms from 2010 - BOREK, DARIUSZ (Prawo Kanoniczne, 2014)
The present article analyses delicta graviora contra mores, that is the crimes reserved to the Congregation for the Doctrine of the Faith in De delictis reservatis Norms from 2010 concerning morals, namely sexual abuse of minors, as well as child pornography. The first of the crimes contra mores is sexual abuse committed by a cleric with regard to minors and other subjects with permanently imperfect use of reason. It comprises all the forms of sexual abuse, ranging from showing pornographic materials, uttering improper comments, through inappropriate touching or kissing, to a physical contact or even a full sexual penetration. Such crimes deserve the strictest consequences, especially when they are committed by clergy towards children or youth entrusted in their custody. The latter category of crimes discussed in this article is the one of child pornography which is, according to De delictis reservatis Norms from 2010, purchasing, storing and distributing for indecent purposes pornographic pictures with minors under fourteen years of age done by a cleric in any way and using any instruments. Pornography is an internally immoral act, especially in the case of child pornography, and one should not be surprised that the discussed crime has been classified into the delicta reservata category. Both of the crimes discussed in the article are the cases of so called delicta propria, that is the crimes whose offenders may be only clergy, which does not exclude a possibility of penal responsibility of potential co-offenders, according to the rules stated in Canon 1329. Summing up, it should be stated that both keeping the existing instructions in the delicta graviora contra mores matter and introducing some changes and innovations indicate great concern of the Church for the protection of morals in regard to the sixth commandment of the Decalogue. Particularly important becomes visible concern of the Church for the protection of minors and subjects legally equal to them against any form of sexual abuse.